Growth, Export Performance and Trade Competitiveness of Lentil (Lens culinaris) From Nepal - Ghimire, Binod; Dhakal, Shiva Chandra; Marahatta, Santosh; Bastakoti, Ram Chandra (International Journal of Social Sciences and Management, 2024)
The lentil (Lens culinaris) sector in Nepal has realized as an export potential commodity but lacks adequate trade related research and development. To study the growth, export performance and trade competitiveness of Nepalese lentil, secondary data pertaining for the period of 30 years (1990–2019 A.D.) were analyzed classifying as pre and post WTO period for Nepal. Compound annual growth rate (CAGR), Cuddy-Delle Velle instability index, export performance ratio, reveled comparative advantage (RCA), trade specialization and Herfindahl-Hirschman index were analyzed. The trend analysis showed highly fluctuation with the growth rate of 40.31 and 42.24 percent per annum has been noticed in import value and quantity respectively. Whereas; the export quantity is found negative growth of 0.43 percent and export value with the growth of 1.44 percent. High instability was found in all parameters of export and import and highest variation was noticed for pre-WTO period in comparison to post-WTO. Nepal enjoys relatively strong competitiveness in export of lentil with RCA value greater than 1. Trade specialization index fluctuated over the years, it remains in the stage of import substitution declining from growth stage and have witnessed positive direction to revive the lentil export performance from Nepal. Herfindahl-Hirschman index showed that the Nepalese lentil market for export is highly concentrated which can lead to high economic risks. Int. J. Soc. Sc. Manage. Vol. 11, Issue-(1-2): 7-16.